A flow model in bulk metallic glasses. (1st January 2023) - Zhang, H.; Wang, Z.; Yang, H.J.; Shi, X.H.; Liaw, P.K.; Qiao, J.W.
Abstract: Based on the microscopic mechanisms applicable to bulk metallic glasses (BMGs), such as the free-volume theory and fracture theory of brittle solids, a constitutive equation for the crack-like propagation velocity of shear bands in BMGs is deduced, ν SBcl = ν 0 a 0 exp ( − E S / k T ) . Furthermore, a flow model of monolithic BMGs is successfully established, log ν SB = log ( ν 0 a 0 ) + log e E S / ( k T l ) − log e E S / ( k T ) . The model explains clearly the fundamental deformation of BMGs at the temperature far below the liquidus temperature, i.e., the mechanism of serrated flows. Not only does the model accurately predict the transition between serrated and non-serrated flows, but the Arrhenius equation and activation energy received by the current model for most BMGs are consistent with the experimental results. The current study paves a way to plastically process BMGs, avoiding catastrophic plasticity instability. Graphical Abstract: Image, graphical abstract